Evaluation and prediction of carbon fiber–reinforced polymer cable anchorage for large capacity. Issue 8 (June 2019) - Feng, Bo; Wang, Xin; Wu, Zhishen
Aiming to address the problems of stress concentration on conical wedge anchorage, a fiber-reinforced polymer cable anchorage with segmental variable stiffness of the load transfer medium was proposed. The key parameters that affect the anchorage behavior were investigated. The mechanical properties of the carbon fiber–reinforced polymer tendon and load transfer medium were tested. The failure mode, anchoring efficiency, stress, and displacement in the anchor zone were studied. The parameter optimization was performed using an experimentally verified finite element simulation. The parameters of the anchorage system with large capacity were evaluated. The results demonstrate that the compressive strength of the load transfer medium is the designed stress limit for the anchorage system. The cable does not slip or become damaged in the anchor zone, and the anchoring efficiency reaches 91%. The distribution of the shear and radial stress on the cable surface is smooth, and the stress concentration is greatly relieved. The result of the finite element simulation is consistent with the experimental values when the friction coefficient is 0.15, and the material and geometric parameters of the anchorage system with cable forces of 5000, 10, 000, 15, 000, and 20, 000 kN are suggested. The geometric parameters of the anchor system with diverse cable capacity can be preliminarily designed based on the fitting equations.